2020
DOI: 10.1590/1678-4499.20190387
|View full text |Cite
|
Sign up to set email alerts
|

Validation of white oat yield estimation models using vegetation indices

Abstract: The use of remote sensing in agriculture presents some practical applications in crop production forecast. In this context, studies with remote sensing are scarce for crops such as white oats, which may indicate the capacity of using this technique in the crop. The aim of this study was to evaluate the accuracy in validation of white oat biomass and grain yield estimates by spectral models previously calibrated using two vegetation indices (NDVI and IRVI) at three phenological stages. The mean values of NDVI a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Also, other researchers have indicated that NDVI has a stronger correlation when estimating white oat grain yield in comparison to other VI's. 35,36…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, other researchers have indicated that NDVI has a stronger correlation when estimating white oat grain yield in comparison to other VI's. 35,36…”
Section: Resultsmentioning
confidence: 99%
“…Also, other researchers have indicated that NDVI has a stronger correlation when estimating white oat grain yield in comparison to other VI's. 35,36 Evaluation of thematic yield maps by kernel density estimation Yield maps using estimated and actual oats grain yield were generated by the statistical pattern analysis method of KDE. The oats grain yield map variation was highlighted as follows: low (red = 0-4.97 t per ha), medium (orange = 4.97-6.18 t per ha), high (yellow = 6.18-7.11 t per ha) and very high (green > 7.62 t per ha) yield areas.…”
Section: Correlation Between Estimated and Actual Oats Grain Yieldmentioning
confidence: 99%
“…maize in Bolton and Friedl, 2013; winter wheat, sorghum and corn in Kogan et al, 2012), South America (e.g. white oat in Brazil in Coelho et al, 2020), Europe (e.g. maize in Germany in Bachmair et al, 2018;cereals in Spain in García-León et al, 2019), Asia (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Some have looked specifically at agricultural droughts with efforts to validate drought indices using crop yield data (e.g. Brazil: Coelho et al, 2020;Spain: García-León et al, 2019;Ethiopia: Moussa Kourouma et al, 2021;U.S. : Peña-Gallardo et al, 2018).…”
mentioning
confidence: 99%